Listy Zygmunta Celichowskiego do Alfonsa Parczewskiego - Andrysiak, Ewa (Biblioteka Uniwersytecka w Poznaniu, 2011)
Artykuł przedstawia, zachowane w Litewskim Państwowym Archiwum Historycznym w Wilnie, listy Zygmunta Celichowskiego do Alfonsa Parczewskiego, związane z prowadzoną przez nich działalnością społeczną.

This article discusses letters written by Zygmunt Celichowski to Alfons Parczewski. The letters are currently held in the Lithuanian Archives of Old Records in Vilnius. The letters concern the social activity performed by both the author and the recipient.
Letter exchange between Zygmunt Celichowski and Alfons Parczewski
Keywords: Zygmunt Celichowski; Alfons Parczewski; Korespondencja; Epistolography